2020
DOI: 10.1080/21505594.2020.1726570
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome in childhood Plasmodium falciparum malaria

Abstract: Plasmodium falciparum malaria is classified as either uncomplicated or severe, determining clinical management and providing a framework for understanding pathogenesis. Severe malaria in children is defined by the presence of one or more features associated with adverse outcome, but there is wide variation in the predictive value of these features. Here we review the evidence for the usefulness of these features, alone and in combination, to predict death and other adverse outcomes, and we consider the role th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 225 publications
0
21
0
Order By: Relevance
“…Therefore, it is of great significance to research new prognosis-related genes for prognosis assessment and treatment guidance for BC and its different subtypes. In our study, low expression of ZNF385B has shown important prognostic value in different subtypes, which might be used to evaluate the risk and prognosis of subgroups and guide beneficial individual treatment options for patients with high risk of death or worse prognosis [24].Currently, surgery has been regarded as an important measure for malignant tumor. However, the possibility of recurrence especially in basal-like BC could adversely influence the outcome of patients.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, it is of great significance to research new prognosis-related genes for prognosis assessment and treatment guidance for BC and its different subtypes. In our study, low expression of ZNF385B has shown important prognostic value in different subtypes, which might be used to evaluate the risk and prognosis of subgroups and guide beneficial individual treatment options for patients with high risk of death or worse prognosis [24].Currently, surgery has been regarded as an important measure for malignant tumor. However, the possibility of recurrence especially in basal-like BC could adversely influence the outcome of patients.…”
Section: Discussionmentioning
confidence: 70%
“…In children with severe malaria, metabolic acidosis is present in up to 50% of cases, and is strongly associated with a fatal outcome (10,14,15). Metabolic acidosis in Malaria is mainly a result of increased lactate (LA) production from anaerobic glycolysis and to a smaller extent from P. falciparum parasites (5,8).…”
Section: Resultsmentioning
confidence: 99%
“…Despite prompt administration of anti-malarials, 5.8%–24% of childhood deaths from severe malaria occur on the first day of admission [ 2 , 3 ]. Metabolic acidosis and acute kidney injury are two of three (in addition to coma) complications of malaria most predictive for a fatal outcome of severe malaria [ 2 , 4 10 ]. However, diagnosis of metabolic acidosis or acute kidney injury requires laboratory facilities beyond the basic test facilities often available.…”
Section: Introductionmentioning
confidence: 99%
“…In children with severe malaria, metabolic acidosis is present in up to 50% of cases, and is strongly associated with a fatal outcome [ 10 , 14 , 15 ]. Metabolic acidosis in malaria is mainly a result of increased lactate (LA) production from anaerobic glycolysis and to a smaller extent from Plasmodium falciparum parasites [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation